Protocol for generating human assembloids to investigate thalamocortical and corticothalamic synaptic transmission and plasticity - Anjana Nityanandam; Mary H. Patton; Ildar T. Bayazitov; Kyle D. Newman; Kristen T. Thomas; Stanislav S. Zakharenko (STAR Protocols)
Summary: Human induced pluripotent stem cells (hiPSCs) can be used to generate assembloids that recreate thalamocortical circuitry displaying short-term and long-term synaptic plasticity. Here, we describe a protocol for differentiating hiPSCs into thalamic and cortical organoids and then fusing them to generate thalamocortical assembloids. We detail the steps for using whole-cell patch-clamp electrophysiology to investigate the properties of synaptic transmission and synaptic plasticity in this model system.For complete details on the use and execution of this protocol, please refer to Patton et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.